2006
DOI: 10.1590/s0066-782x2006001900011
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensão arterial na população adulta de Salvador (BA) - Brasil

Abstract: Objective: To estimate the prevalence of hypertension (H) and its association with other cardiovascular risk factors in a highly multiracial population. Methods:A cross-sectional study carried out in Salvador, Brazil, in a population sample of 1439 adults ≥ 20 years of age. All participants completed a questionnaire at home and had the following measurements taken: blood pressure, body weight, height, waist circumference (WC), and serum glucose and lipids. Hypertension was defined as mean SBP ≥140 and/or DBP ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1
57

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 21 publications
5
36
1
57
Order By: Relevance
“…We observed a direct association between prevalence of hypertension and age, in accordance with other studies 5,[10][11][12][13][14][15] . Regarding schooling, there was an inverse association with the prevalence of hypertension, which is in agreement with the results obtained in several studies 12,[15][16][17] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed a direct association between prevalence of hypertension and age, in accordance with other studies 5,[10][11][12][13][14][15] . Regarding schooling, there was an inverse association with the prevalence of hypertension, which is in agreement with the results obtained in several studies 12,[15][16][17] .…”
Section: Discussionsupporting
confidence: 93%
“…Regarding schooling, there was an inverse association with the prevalence of hypertension, which is in agreement with the results obtained in several studies 12,[15][16][17] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lessa et al 31 estimated the prevalence of and the factors associated with hypertension in a sample of adults from Salvador (BA). The total prevalence of hypertension was 29.9%, and in women, the prevalence was 31.7% (95%CI: 28.5 to 34.9), which is similar to the prevalence of hypertension in maroons found by the present study (34.9%).…”
Section: Crevelaromentioning
confidence: 99%
“…Studies carried out in Brazil 23,24 have shown that, usually, non-white are more commonly hypertensive than white individuals. A study with North-American Adventists 25 has found that 33.6% of black individuals are hypertensive, while the prevalence of hypertension in white individuals was 25.4% (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%